Deviation without Contradiction in Adolf Reinach’s Ontology - Di Lucia, Paolo (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Is it possible to affirm the existence of eidetic a priori laws, if these laws can be contradicted by positive law propositions? How is it possible a deviation from a priori juridical propositions? These are the two questions to which the present paper “Deviation without contradiction in Adolf Reinach’s ontology” is devoted. The aim of the paper is to analyse the relations between a priori juridical propositions and propositions of positive law as investigated by Adolf Reinach. The Author presents and illustrates Adolf Reinach’s conception of conditioned a priori connections.